The Role of Advertising and Price Fairness in Purchasing Decisions at Salons and Barbershops - Nazmul Irfandi; Librina Tria Putri; Desmawati Desmawati (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
The beauty and personal care service industry has experienced significant growth in recent years, resulting in increasingly intense competition among salons and barbershops. To remain competitive, business owners are required to implement effective marketing strategies that can attract consumers and encourage purchasing decisions. This study aims to examine the role of advertising and price fairness in purchasing decisions at salons and barbershops. This research employed a quantitative approach using a survey method. The population consisted of customers who had utilized salon and barbershop services in Bangkinang Kota. A total of 90 respondents were selected using accidental sampling techniques. Data were collected through questionnaires and analyzed using multiple linear regression. The findings indicate that advertising and price fairness simultaneously have a positive and significant effect on purchasing decisions. Partially, advertising has a positive and significant effect on purchasing decisions. Likewise, price fairness also has a positive and significant effect on purchasing decisions. The results imply that effective advertising and fair pricing perceptions are important factors in influencing customer purchasing decisions in the salon and barbershop service industry.